Analisis Minat Anggota dalam Menggunakan Produk Sajadah Berhadiah di BMT NU Cabang Pragaan - Faizzatul Ainiyah Utami (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
BMT NU (Baitul Maal wa at-Tamwil Nuansa Ummah) is a microfinance institution based on Islamic sharia principles and cooperatives. This institution aims to improve the economic welfare of the community through various financial products and services that are in accordance with Islamic values. One of its flagship products is SAJADAH (Wadīʻah Term Deposit with Prizes), which uses the Wadīʻah Yaḍ Ḍamānah contract. In this contract, funds deposited by customers are safeguarded by the BMT, and although there is no obligation from the institution to provide returns, customers still receive direct prizes as a form of appreciation. The prizes awarded vary, ranging from electronics and household appliances to precious metals such as gold. Uniquely, they are not drawn through a lottery system, so every eligible customer can receive them immediately. Based on internal data from BMT NU, the number of members participating in the SAJADAH program has decreased from 2019 to early 2023. This is an important background in the research that focuses on three main aspects: the level of member interest in SAJADAH products, inhibiting factors, and supporting factors for this interest. This research uses a qualitative descriptive approach, with data collection techniques including field observations, direct interviews with members and managers, and analysis of official documentation from the institution. The results show that public interest in SAJADAH products is in the moderate category, with the majority of interested parties coming from the middle to upper class who have more stable financial capabilities. Several main inhibiting factors are the large nominal savings required to receive prizes, as well as the relatively long withdrawal period, which is considered less flexible by some members.